English Borrowing in Indonesian Language Spoken by Indonesian Teenagers in Junior High School - Restu Anggi Gustara (Universitas Pendidikan Indonesia (UPI), 2015)
This study looks specifically at the borrowing words phenomenon among teenagers in one junior high school in Bandung. The borrowing words phenomenon being inverstigated in this study included the types of borrowing words, phonological process, the most dominant part of speech in borrowing words and some possible factors for borrowing to occur. The data were taken from 18 teenagers from three different grades. The seventh grade consists of six teenagers (11-12 years old), eighth grade consists of six teenagers (12-13 years old) and ninth grade consists of six teenagers (13-14 years old). The data were analyzed in a descriptive qualitative method by using the theories from Hoffer (2005), Campbell (1998), Field (2002) and Thomas (1993). The findings showed that the most frequent type of borrowing in all grades is loanword. In terms of phonological processes, the most frequent sound change occurs in the borrowing is Monophthongisation. With regard to parts of speech, noun appears as the dominant part of speech in the borrowing words. Four possible factors that cause borrowing words in teenagers are due to the frequency in using borrowing words, the number of speakers around the respondents, the habitual of expressing the English words and the low competence of the speakers. In conclusion, it seems apparent that borrowing words in this context udergo many phonological adaptations.Keywords: borrowing words, loanword, sound change, factors of borrowing words